Містечка України - Гудченко, З. (Народна творчість та етнографія, 2006)
The article discusses the following topic from the viewpoint of the history, presenting several theories of the emergence of the towns on the territory of Ukraine. The towns (their buildings and way of life) can he characterized as a specific phenomenon, brought to life by historical, social, and economic conditions. Their uniqueness can be traced in the structure, planning, the principles of the forming of the street space, harmonic combination of the buildings with natural landscapes.